DIGITAL MORAL DISRUPTION IN ISLAMIC RELIGIOUS EDUCATION: CHALLENGES AND STRATEGIES IN THE AI ERA AT BLITAR REGENCY HIGH SCHOOLS: CHALLENGES AND STRATEGIES IN THE AI ERA AT BLITAR REGENCY HIGH SCHOOLS - Miftakhul Rohman; Doni Saputra; Marwan Hayeemaming (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
The rapid growth of digital technology and artificial intelligence has transformed the educational landscape, creating both opportunities and challenges, particularly in moral and character development. Islamic Religious Education (PAI), which aims to foster spiritual awareness and cultivate noble character, is increasingly challenged by digital culture, which is often value-neutral and sometimes misaligned with Islamic ethical principles. This study examines the phenomenon of digital moral disruption in the implementation of PAI learning in public senior high schools in Blitar Regency. This study employs a qualitative case study approach to explore the phenomenon within its real-life context. The participants include PAI teachers, students, school principals, and other relevant stakeholders. Data were collected through participatory observation, in-depth interviews, and document analysis. The data were analyzed using the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. The findings indicate that digital moral disruption affects students’ attitudes and learning behaviors through excessive smartphone use, increased reliance on digital information, and reduced face-to-face interaction. These factors hinder the effective internalization of Islamic values in the learning process. This study offers important practical implications. Teachers should integrate digital literacy and ethical guidance into PAI instruction while reinforcing their role as moral exemplars. Policymakers should support curriculum development that balances technological competence with character education and provide professional development programs to help teachers address digital challenges effectively. Strengthening digital ethics and promoting responsible technology use are essential to sustain students’ moral development in the digital era.